Duffy blood group phenotypes/genotypes and their association with malaria prevalence in four communities of northwest Ecuador - Veloz Haro, Elizabeth Verónica (PUCE, 2016)
Ecuador is in malaria pre-elimination phase, with a reduction of more than 99% in the incidence of confirmed cases that were reported between 2000 and 2013. In Ecuador malaria is caused by Plasmodium vivax and P. falciparum protozoan species. Invasion of erythrocytes is essential for the development of the disease in the human host. P. vivax requires a specific interaction with antigens Fya or Fyb, corresponding to the Duffy receptor in the red blood cells. The Duffy polymorphism affects P. vivax ability to invade erythrocytes. This study aimed to determine the malaria prevalence and the composition of Duffy polymorphisms of the population of four communities of San Lorenzo county in northwest Ecuador. Methodology/Findings Blood samples from a total of 797 individuals were collected in El Pedregal, Ricaurte, La Boca and El Guadual communities in northwest Ecuador. Plasmodium detection and Duffy allele genotyping were performed by qPCR. The malaria prevalence in 2015 was compared to previously report in 2013. We found 4.5% malaria prevalence in 2015 that was lower than the reported prevalence for 2013. Most of positive infections (77.8%) were caused by P. vivax and 97.3% were asymptomatic. San Lorenzo population had 70.4% of Duffy positive phenotypes prevalence and 29.6% of Duffy negative phenotype prevalence. Six cases of P. vivax infected individuals with a Duffy negative genotype were found. Conclusions The results show a high prevalence of asymptomatic malaria in Northwest Ecuador being P. vivax the most frequent species detected. Moreover, the Duffy blood group system in the study sites is highly heterogeneous, with three alleles FY*A, FY*B and FY*BES present. In addition, we report for the first time in the pacific region of South America Duffy negative individuals infected with P. vivax. Taken together, the results show that the situation of malaria in northwest Ecuador is far from understood.